0078 Work organisational characteristics and psychological distress in French call-centres. Is there a direct effect?. (23rd June 2014) - Boini, Stephanie; Chouaniere, Dominique; Wild, Pascal
Abstract : Objectives: In cross sectional studies, relationships between perceived stressors and self-reported health are suspected of mono-method bias related to negative affectivity. The purpose of this work was to test if work organisational characteristics (WOC) reported by managers were related to psychological distress (PD) reported by call-handlers, taking into account their perception of work conditions (perceived strain) and usual individual confounders. Method: Managers of 107 call-centres were queried by occupational physicians on their call-centres' WOC. 4002 call-handlers (2, 929 women were considered here) of these call-centres completed self-reported questionnaires in order to evaluate perceived work strain (Karasek and Siegrist questionnaires) and PD (12-items General Health Questionnaire). A 2-level analysis tested the relationships between 14 WOC and PD score, with and without adding perceived strain as confounder, assuming that unchanged coefficients between WOC and PD score flag a direct effect of WOC on psychological distress. We also analysed perceived strain as an effect modificator for WOC using interactions. Results: Five of 14 WOC were significantly related to the PD score: type of calls, call-centre size, number of activity parameters displayed on screen, instructions for client relationships, and required control role of supervisor. In adding perceived strain, the relationship only remained for the type of call. Conclusions: Main results of this study are (1) existence of relationships between WOC reported by managers and psychological distress reported by call-handlers (2) most of effects of WOC are moderated by the perception of work strain.